HyRAD-X Exome Capture Museomics Unravels Giant Ground Beetle Evolution. (14th May 2021) - Toussaint, Emmanuel F A; Gauthier, Jérémy; Bilat, Julia; Gillett, Conrad P D T; Gough, Harlan M; Lundkvist, Håkan; Blanc, Mickael; Muñoz-Ramírez, Carlos P; Alvarez, Nadir
Abstract: Advances in phylogenomics contribute toward resolving long-standing evolutionary questions. Notwithstanding, genetic diversity contained within more than a billion biological specimens deposited in natural history museums remains recalcitrant to analysis owing to challenges posed by its intrinsically degraded nature. Yet that tantalizing resource could be critical in overcoming taxon sampling constraints hindering our ability to address major evolutionary questions. We addressed this impediment by developing phyloHyRAD, a new bioinformatic pipeline enabling locus recovery at a broad evolutionary scale from HyRAD-X exome capture of museum specimens of low DNA integrity using a benchtop RAD-derived exome-complexity-reduction probe set developed from high DNA integrity specimens. Our new pipeline can also successfully align raw RNAseq transcriptomic and ultraconserved element reads with the RAD-derived probe catalog. Using this method, we generated a robust timetree for Carabinae beetles, the lack of which had precluded study of macroevolutionary trends pertaining to their biogeography and wing-morphology evolution. We successfully recovered up to 2, 945 loci with a mean of 1, 788 loci across the exome of specimens of varying age. Coverage was not significantly linked to specimen age, demonstrating the wide exploitability of museum specimens. We also recovered fragmentary mitogenomes compatible with Sanger-sequenced mtDNA. Our phylogenomic timetree revealed a Lower Cretaceous origin for crown group Carabinae, with the extinct Aplothorax Waterhouse, 1841 nested within the genus Calosoma Weber, 1801 demonstrating the junior synonymy of Aplothorax syn. nov., resulting in the new combination Calosoma burchellii (Waterhouse, 1841) comb. nov. This study compellingly illustrates that HyRAD-X and phyloHyRAD efficiently provide genomic-level data sets informative at deep evolutionary scales.